HUBUNGAN TINGKAT PENGETAHUAN DENGAN KEPATUHAN IBU DALAM PEMBERIAN IMUNISASI DASAR PADA BAYI DI PUSKESMAS KECAMATAN CENGKARENG JAKARTA BARAT - Desnita; Yanuar (Jurnal Nurse, 2022)
The immunization program has large leverage to improve community health status, because the majority of infant mortality can be prevented by immunization interventions. One effort to improve children's immunity is the giving basic immunization. In immunization programs mother's role is the most important, knowledge of mothers about immunizations influence the implementation immunization itself. To maximize the results of the immunization, it should be given routinely. The purpose of this study was to determine the relationship between the level of knowledge with obedience mother in giving of basic immunization to infants. This research method is descriptive correlation with a quantitative approach. The population in this study were mothers who had babies to immunization in Puskesmas Cengkareng, West Jakarta. The number of samples obtained 50 respondents. Data were collected by questionnaire. Data analysis using chi-square test with p-value (> 0.05). The results showed 46 respondents were knowledgeable of both adherent in the giving of basic immunization 43 respondents (93.5%) and less adherent knowledgeable three respondents (6.5%) of 4 respondents. Statistical test results obtained with chi square p-value 0.191 (> 0.05). There is no significant relationship between the level of knowledge of mothers with maternal compliance in the provision of basic immunization in infants. Because, basically, mothers who have very high awareness of immunization.